Effect of Phoenix Dactylifera Spathe Hydroalcoholic Extract on Chronic Pain in Mice - M.H Dashti-R; A.R Vahidi; M.S Panjalizadeh (Institue of Medicinal Plants, ACECR, 2012)
Background: In Persian traditional medicine, many medicinal plants have been used as analgesics in which one of them is the distillate of Phoenix Dactylifera Spathe (PDS) known as "Tarooneh". Objective: This study was conducted to assess the antinociceptive effect of Tarooneh (PDS) hydro alcoholic extract on inflammatory pain induced by formaline in mice. Methods: In this study, 28 male albio mice weighting 25 - 30 grams, were randomly and equally divided into 4 groups. 2, 20 and 200 mg/kg PDS extract and vehicle were administered intraperitomeally to the test and control groups respectively in a volume of 10 ml/kg. Animals were subjected to Formalin test as an animal model for inflammatory pain assessment. Results: Mean pain score induced by formalin test in control group was 1.665 ± 0.0599 while in test groups receiving 2, 20 and 200 mg/kg PDS extract were 1.079 ± 0.0666, 0.9192 ± 0.0822 and 0.3842 ± 0.0658 respectively. Conclusion: data from this study revealed that PDS extract, significantly and dose dependently, attenuated the inflammatory formalin induced pain in mice.